Israel's Declaration of Independence : the history and political theory of the nation's founding moment - Rogachevsky, Neil, 1982- 1982- (Cambridge University Press, 2023)
"Israel's Declaration of Independence is the first book-length treatment of the history and political thought of Israel's founding text. Through a presentation of the drafts of Israel's Declaration of Independence in English for the first time, Neil Rogachevsky and Dov Zigler examine the political and theoretical dilemmas faced by the founders of Israel as they prepared to declare independence. The issues at stake began with war, strategy, survival, and great power diplomacy, and ascended to the nature of rights, the relationship of religion and state, and the meaning of political sovereignty. The volume documents how the Declaration of Independence evolved and changed over several drafts. On May 14, 1948, Israel's first Prime Minister David Ben-Gurion declared that it "is the natural right of the Jewish people to be masters of their own fate, like all other nations, in their own sovereign State." With those words, he changed the trajectory of a nation and a region"